(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
On the basis of determining the degree of variability, correlative dependence and resistance to wilt of introgressive ridges in different soil and climate conditions, the ridges with high yield, quick ripening, fiber yield of 41.0-43%, quality indicators and high adaptability were selected. "S-6782" variety, which has a high index of valuable economic traits among their populations, was selected as a variety resistant to adverse factors of the external environment when new medium-fiber introgressive varieties were grown under the same conditions in different soil-climatic conditions of our republic.